Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b)
\(2x\cdot\left(2x-3\right)=\left(3-2x\right)\cdot\left(2-5x\right)\\ \Leftrightarrow-2x\cdot\left(3-2x\right)-\left(3-2x\right)\cdot\left(2-5x\right)=0\\ \Leftrightarrow\left(3-2x\right)\cdot\left(-2x-2+5x\right)=0\\ \Leftrightarrow\left(3-2x\right)\cdot\left(3x-2\right)=0\\ \Rightarrow\left[{}\begin{matrix}3-2x=0\\3x-2=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=\frac{3}{2}\\x=\frac{2}{3}\end{matrix}\right.\)
c)
\(2x^3+6x^2=x^2+3x\\ \Leftrightarrow2x^3+6x^2-x^2-3x=0\\ \Leftrightarrow x\cdot\left(2x^2+6x-x-3\right)=0\\ \Leftrightarrow x\cdot\left(-3+6x-x+2x^2\right)=0\\ \Leftrightarrow x\cdot\left[-3\cdot\left(1-2x\right)-x\cdot\left(1-2x\right)\right]=0\\ \Leftrightarrow x\cdot\left(-3-x\right)\cdot\left(1-2x\right)=0\\ \Rightarrow\left[{}\begin{matrix}x=0\\-3-x=0\\1-2x=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=0\\x=-3\\x=\frac{1}{2}\end{matrix}\right.\)
d)
\(x^2-5x+6=0\\ \Leftrightarrow x^2-3x-2x+6=0\\ \Leftrightarrow6-2x-3x+x^2=0\\ \Leftrightarrow2\cdot\left(3-x\right)-x\cdot\left(3-x\right)=0\\ \Leftrightarrow\left(2-x\right)\cdot\left(3-x\right)=0\\ \Rightarrow\left[{}\begin{matrix}2-x=0\\3-x=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=2\\x=3\end{matrix}\right.\)
e)
\(\left(2x+5\right)^2=\left(x+2\right)^2\\ \Leftrightarrow\left(2x+5\right)^2-\left(x+2\right)^2=0\\ \Leftrightarrow\left(2x+5+x+2\right)\cdot\left(2x+5-x-2\right)=0\\ \Leftrightarrow\left(3x+7\right)\cdot\left(x+3\right)=0\\ \Rightarrow\left[{}\begin{matrix}3x+7=0\\x+3=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=-\frac{7}{3}\\x=-3\end{matrix}\right.\)
a) \(\left(x+3\right)\left(x+5\right)+\left(x+3\right)\left(3x-4\right)=0\)
➜\(\left(x+3\right)\left(x+5+1+3x-4\right)=0\)
➜\(\left[{}\begin{matrix}x+3=0\\x+3x=2\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-3\\x=\frac{1}{2}\end{matrix}\right.\)
Mk đang hok zoom sorry nha!!!
a) \(6x^2-x-1\)
\(=6x^2-3x+2x-1\)
\(=3x\left(2x-1\right)+\left(2x-1\right)\)
\(=\left(3x+1\right)\left(2x-1\right)\)
a) \(x^3-3x^2-x+3\) \(=\left(x^3-x\right)-\left(3x^2-3\right)=x\left(x^2-1\right)-3\left(x^2-1\right)\)
\(=\left(x-3\right)\left(x^2-1\right)\)
b) \(x^3-4x^2-x+4=\left(x^3-x\right)-\left(4x^2-4\right)=x\left(x^2-1\right)+4\left(x^2-1\right)\)
\(=\left(x-4\right)\left(x^2-1\right)\)
c) \(2x^3-x^2-2x+1=\left(2x^3-2x\right)-\left(x^2-1\right)=2x\left(x^2-1\right)-\left(x^2-1\right)\)
\(=\left(2x-1\right)\left(x^2-1\right)\)
d) \(5x^3-x^2-5x+1=\left(5x^3-5x\right)-\left(x^2-1\right)=5x\left(x^2-1\right)-\left(x^2-1\right)\)
\(=\left(5x-1\right)\left(x^2-1\right)\)
a/ \(x\left(x^2-2x-2\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x=1\pm\sqrt{3}\\\end{matrix}\right.\)
b/ \(\Leftrightarrow2x^3-4x^2+6x-x^2+2x-3=0\)
\(\Leftrightarrow2x\left(x^2-2x+3\right)-\left(x^2-2x+3\right)=0\)
\(\Leftrightarrow\left(2x-1\right)\left(x^2-2x+3\right)=0\)
c/ \(\Leftrightarrow3x^3-15x^2+9x+x^2-5x+3=0\)
\(\Leftrightarrow3x\left(x^2-5x+3\right)+\left(x^2-5x+3\right)=0\)
\(\Leftrightarrow\left(3x+1\right)\left(x^2-5x+3\right)=0\Rightarrow\left[{}\begin{matrix}x=-\frac{1}{3}\\x=\frac{5\pm\sqrt{13}}{2}\end{matrix}\right.\)
d/ \(x\left(x^2+6x-5\right)=0\Rightarrow\left[{}\begin{matrix}x=0\\x=-3\pm\sqrt{14}\end{matrix}\right.\)
1,4x2.(5x3+2x-1)
=4x2.5x3+4x2.2x-4x2.1
20x5+8x3-4x2
2,4x3y2:x2
=4xy2
3,(15x2y3-10x3y3+6xy):5xy
15x2y3:5xy-10x3y3:5xy+6xy:5xy
3xy2-2x2y2+\(\dfrac{6}{5}\)
\(2x^3+x^2+5x-3\)
\(=\left(2x^3-x^2\right)+\left(2x^2-x\right)+\left(6x-3\right)\)
\(=x^2\left(2x-1\right)+x\left(2x-1\right)+3\left(2x-1\right)\)
\(=\left(2x-1\right)\left(x^2+x+3\right)\)